SPONSOR-ORIENTED MARKETING COMMUNICATION BY PADANG TV FOR MAINTAINING LOCAL-CULTURAL CONTENT - Nindika Widya Tirta; Elva Ronaning Roem; Alna Hanana; Yayuk Lestari (Universitas Bunda Mulia, 2020)
This research focuses on promotional strategies conducted by Padang TV in an effort to introduce and maintain the Duduak Baselo program as a cultural content program. From the minimal existence of cultural content in the majority of Indonesian television, Padang TV is one of the local stations that present cultural content, one of which is the Duduak Baselo program. This program can survive, of course, because there are promotional and marketing efforts undertaken by the television station. Promotional mix analysis that becomes the focus of this research is on how the station approach to sponsors. This research uses descriptive qualitative method with a case study approach. In-depth interviews, observations, and documentation are used in collecting data. The data obtained were then processed with Miles and Huberman's technical analysis and validated with triangulation techniques. The results of this study indicate that the Duduak Baselo program carries out several communication activities as their promotional strategies in introducing and maintaining the Duduak Baselo program. Padang TV, as the station that produces Duduak Baselo, in such a way builds cooperative relationships with various parties, such as the government and the private sectors. This collaborative relationship is developed to get sponsors/advertisers. Activities undertaken to establish cooperation include building relationships, spreading proposals, lobbying, and negotiating.